Komitmen Manajemen, Pemasaran Internal, Kepuasan Kerja Karyawan dan Perilaku Positif Karyawan dalam Mempengaruhi Kualitas Pelayanan Rumah Sakit (Studi pada Rumah Sakit Tipe B dan C di Kalimantan Tengah) - Sintani, Lelo (Universitas Brawijaya, Indonesia, 2009)
This research aims to know and evaluate the influence of 1) management commitment on service quality both direct and indirect through internal marketing, employee job satisfaction and employee positive attitude; 2) internal marketing on service quality direct and indirect through employee job satisfaction and employee positive attitude; 3) employee job satisfaction on service quality direct and indirect throuht employee positive attitude, 4) employee positive attitude on service quality. Population of the research are all functional or section medical staffs, financial and supporting instalation section staffs that have close relation with customer in Rumah Sakit Umum Daerah (RSUD) of B and C types in Center Kalimantan. Sample unit of service provider is management (leader of SMF or leader of section and installation units who provide direct service to customer), medical employee (doctor,nurse, and other mrdical employee) and non-medical employee-and customer - patients and their families. Technique of collecting data is done by using three mean-for management level by using census, for medical and non-medical staffs by using accidental and for customer by using purposive sampling. Data are then analyzed by using descriptive analysis and inferential statistic. To evaluated the influence among variables, the research uses structural equation model (SEM) analysis with partial least square (PLS). Result of the research prove that management commitment has direct significant influence on service quality, internal marketing, employee job satisfaction and employee positive attitude. It also influences indirectly significant on service quality and employee positive attitude through internal marketing and employee job satisfaction partially. Internal marketing has direct significant influence on employee positive attitude and service quality but does not have influence on employee job satisfaction. There is not direct influence of internal marketing on employee job satisfaction and employee positive attitude and service quality. Employee job satisfaction has direct significant influence on service quality and employee positive attitude but does not have indirect influence on servece quality through employee positive attitude because employee positive attitude does not have influence on service quality.Keywords: Management Commitment, Internal Marketing, Employee Job Satisfaction, Employee Positive Attitude and Service Quality